Environmental regulation, abatement strategy, and labor income share - Huang, Yanyan; Zhao, Jun; Lan, Jiajun (Frontiers in Environmental Science, 2022)
Firms need to adopt abatement strategies and change their modes of production and resource allocation under the strict environmental policy, which affects the labor income share. Based on the firm-level data of China’s Industrial Enterprise Database and Pollution Emission Database from 1998 to 2013, this study uses the difference-in-differences (DID) framework to test the effects and mechanisms of environmental policy on labor income share with different abatement strategies. We find that the Two Control Zone policy coupled with Environmental Performance Assessment policy (EPA-TCZ policies) in China, significantly increases the labor income share by 2.6% and reduces sulfur dioxide (SO_2) emissions. Mechanism analyses further find that firms primarily adopt abatement strategies of source control and end-of-pipe treatments to cope with environmental regulation, and labor income share is enhanced through the factor-substitute effect and the cost effect. As the result of labor income share, low-skilled firms and state-owned firms are more sensitive to environmental regulation. The results from this study provide an empirical basis for the formulation and evaluation of environmental policies in developing countries.